Patent Openness Decisions and Investment Propensities of Frontier Enterprises in Asymmetric Competition - Chen Liu; Daiqing Yan; Zihao Song; Gandang Shi; Wentao Zhan; Minghui Jiang (Systems)
The patent openness decisions of frontier enterprises and the consequent investment tendencies of laggard enterprises play a significant role in their profitability. Despite the benefits resulting from directly using open patents, in order to capture market share and surpass frontier enterprises, laggard enterprises must decide whether they are going to invest in R&D or expansion. In this context, based on evolutionary game theory and the operational behaviors of both frontier and laggard enterprises, this study constructed a model of enterprise revenue under asymmetric competition, exploring the impact of patent openness with and without government subsidies on enterprise revenue. This study discovered that: (1) when the industry scale is small, frontier enterprises gain significant social effects through patent openness, while laggard enterprises invest in expansion; (2) as the industry scale gradually expands, frontier enterprises tend to prefer not to open their patents, and laggard enterprises gradually shift from imitation to independent innovation when the return on R&D investment increases more than that on expansion investment; and (3) when the R&D costs of laggard enterprises are high, frontier enterprises usually choose not to open their patents, forcing laggard enterprises to turn to investment in expansion. This allows frontier enterprises to reduce the losses from patent openness while enjoying the benefits of reduced industry production costs. This study provides new perspectives on patent openness and investment tendencies with the help of an evolutionary game mechanism and offers managerial policy recommendations.